ADMINISTRATIVE OFFENSES IN THE FIELD OF BANKRUPTCY - ALIEKSIEIENKO, IHOR (Ehrlich’s Journal, 2024)
The article deals with administrative offenses in the field of bankruptcy, in particular, their legal regulation and problems of practical application. Administrative liability of persons controlling a debtor is mainly punitive and does not contribute to reducing property losses of creditors of an insolvent debtor. The liability provided for by the Bankruptcy Law is much more effective in this regard, although its application in practice remains rare. The author examines various types of liability within the framework of a bankruptcy case, which can be conditionally divided into procedural and substantive liability. The author analyzes separately the provisions of the Code of Ukraine on Administrative Offenses (CUAO), in particular, Article 164- 15 “Concealment of Sustainable Financial Insolvency”, which provides for liability for intentional concealment by a citizen-founder or an official of a business entity of its sustainable financial insolvency by submitting false information or failure to file a petition for initiation of bankruptcy proceedings against a legal entity with an economic court within the established time limit. The author has identified problems in the practical application of Art. 164-15 of the Code of Administrative Offenses related to difficulties in identifying and proving administrative offenses. In particular, difficulties arise due to the need to draw up protocols by the internal affairs authorities (the National Police), which do not always have the ability to effectively detect such offenses. The author suggests ways to improve the legislation in the area of administrative warning in the field of bankruptcy, in particular, by strengthening control and monitoring of financial statements of enterprises, more clearly regulating the obligations of managers and founders to file bankruptcy petitions in a timely manner, expanding the powers of supervisory authorities, improving the procedure for bringing to justice and improving the skills of law enforcement officers.